Do IMF-Supported Programs Boost Private Capital Inflows? : The Role of Program Size and Policy Adjustment - Benelli, Roberto (IMF Working Papers; Working Paper ;, 2003)
I analyze empirically whether program size (the size of financial assistance) and policy adjustment matter for the success of IMF-supported programs. I define a program as successful if the initial program projections for net private capital flows are met or exceeded. I find that success is negatively associated with the size of financial assistance, especially in countries with market access, and that projection biases binding constraints on the amount of IMF lending may account for this association. Moreover, policy adjustment seems to have a causal positive effect on the likelihood of program success.